Electronic Health Record-Based Screening for Major Cancers: A 9-Year Experience in Minhang District of Shanghai, China - He, Dandan; Xu, Wanghong; Su, Hualin; Li, Weixi; Zhou, Jie; Yao, Baodong; Xu, Dongli; He, Na (Frontiers in Oncology, 2019)
Background: An electronic health record (e-HR) system has been developed in Minhang District of Shanghai, China, since 2005, making it convenient for local health institutions to provide integrative and comprehensive health care and management for major diseases. Methods: In 2008, an e-HR-based cancer prevention program was initiated to screen multiple cancers including colorectal, gastric, liver, lung, cervical and breast cancers, and provide subsequent health education and health management to cancer patients and high-risk individuals. This study was designed in prospective analysis, based on the constructive analysis of key information, observation of cancer screening and healthcare processes and organizations, and stages of cancers detected by the e-HR-based programs. Results: From 2008 through 2016, health education was conducted for over five million attendances, and more than three million screening tests were performed for eligible residents over 40 years old. A total of 2 948 cancer cases were detected, accounting for 13.3% of all newly-diagnosed cancers in the district during the nine-year period. 30.7% detected cancer cases were at early-stage, significantly higher than 22.9% in cases identified by e-HR based follow-up and 13.8% in cases diagnosed due to signs or symptoms. More than 136 thousand residents were identified as individuals at high risk of cancer and subject to sustainable clinical follow-up and health management. Conclusions: The successful application of e-HR system in cancer prevention and control in Minhang district of Shanghai, China, implies that the system may act as an extendable and sustainable infrastructure for comprehensive health care and services for a broad spectrum of diseases and health events.